2018
DOI: 10.1080/19420862.2018.1532767
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution glycosylation site-engineering method identifies MICA epitope critical for shedding inhibition activity of anti-MICA antibodies

Abstract: As an immune evasion strategy, MICA and MICB, the major histocompatibility complex class I homologs, are proteolytically cleaved from the surface of cancer cells leading to impairment of CD8 + T cell- and natural killer cell-mediated immune responses. Antibodies that inhibit MICA/B shedding from tumors have therapeutic potential, but the optimal epitopes are unknown. Therefore, we developed a high-resolution, high-throughput glycosylation-engineered epitope mapping (GEM) method, which utilizes site-specific in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Our crystal structure revealed that the epitope recognized by 1G4 (residues Asp95-Asn103) immediately follows the GPI-anchoring sequence, suggesting that it is located proximal to the cell membrane. We also used a high-resolution, high-throughput glycosylation-engineered epitope mapping (GEM) method ( 27 ) to map the location of epitopes bound by mAbs from different bins. GEM results showed that the epitopes bound by 1G4 and 6E10 were the most membrane-proximal, meanwhile, the mAbs in the other bins bound to more membrane-distal epitopes (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Our crystal structure revealed that the epitope recognized by 1G4 (residues Asp95-Asn103) immediately follows the GPI-anchoring sequence, suggesting that it is located proximal to the cell membrane. We also used a high-resolution, high-throughput glycosylation-engineered epitope mapping (GEM) method ( 27 ) to map the location of epitopes bound by mAbs from different bins. GEM results showed that the epitopes bound by 1G4 and 6E10 were the most membrane-proximal, meanwhile, the mAbs in the other bins bound to more membrane-distal epitopes (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Current strategies comprise the inhibition of enzymes responsible for shedding as well as blocking the cleavage sites with therapeutic antibodies. Most likely, the efficacy of some of these new drugs will be limited to certain MICA/B alleles which increases the need for reliable genotyping (18,45).…”
Section: Discussionmentioning
confidence: 99%
“…В то же время следует отметить, что изменения в экспрессии белков MICA/B не являются специфической чертой канцерогенеза и могут быть вызваны рядом других факторов (вирусные заболевания, бактериальные инфекции, хроническое воспаление и т.д. [54].…”
Section: Mica/b как прогностические маркеры при онкологических заболе...unclassified